Impact of mucosal healing on long‐term outcomes in ulcerative colitis treated with infliximab: a multicenter experience. Issue 10 (21st March 2013) - Laharie, D.; Filippi, J.; Roblin, X.; Nancey, S.; Chevaux, J.‐B.; Hébuterne, X.; Flourié, B.; Capdepont, M.; Peyrin‐Biroulet, L.
Summary Background Mucosal healing can be achieved with infliximab (IFX). Aim To assess the impact of mucosal healing on long‐term outcomes in patients with ulcerative colitis (UC) when treated with infliximab (IFX) beyond 1 year. Methods All consecutive adult patients with refractory UC receiving maintenance treatment with IFX in five French referral centres were analysed retrospectively. Only patients who had endoscopic evaluation between 6 and 52 weeks following IFX initiation were included. According to their Mayo endoscopic sub‐score, patients were categorised into mucosal healing (sub‐score: 0–1) and no mucosal healing (2–3). Outcome measures were colectomy and IFX failure defined by drug withdrawal due to secondary failure among primary responders. Results Of the 63 patients (30 women; median age: 38 years), 30 (48%) achieved mucosal healing. The median follow‐up duration was 27 (3–79) months. Colectomy‐free survival rates at 12, 24 and 36 months were, respectively, 100%, 96% and 96% in patients with mucosal healing. The corresponding figures were, respectively, 80%, 65% and 65% in patients without mucosal healing (P = 0.004). By multivariate analysis, mucosal healing was the only factor associated with colectomy‐free survival, with an odds ratio of 18.01 (95%CI: 1.58–204.92). IFX failure‐free survival rates at 12, 24 and 36 months were, respectively, 76%, 69% and 64% in patients with mucosal healing, and 44%, 25% and 21% in those without mucosal healing (P = 0.003). Conclusion Patients with refractory UC who achieved mucosal healing after IFX initiation had better long‐term outcomes, with significantly less colectomy and less IFX failure.